2015
DOI: 10.1089/ten.tea.2015.0234
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Stimulation Enhances Heat-Shock Protein 90 and Mineralized Nodule Formation in Mouse Calvaria-Derived Osteoblasts

Abstract: Low-intensity pulsed ultrasound (LIPUS) has demonstrated its positive effects on osteogenic differentiation of mesenchymal stem cells and the proliferation and differentiation of osteoblasts, negative effects on osteoclast growth, and promotion of angiogenesis, leading to improvement of the tissue perfusion. Heat-shock proteins (HSPs) are initially identified as molecules encouraged and expressed by heat stress or chemical stress to cells and involved in the balance between differentiation and apoptosis of ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Although the total number of Iba-1-positive microglia decreased by LIPUS, phagocytosis was rather enhanced in the LIPUS-treated group. Besides, Hsp 90, which is known to inhibit aggregation of Ab [28], was enhanced by LIPUS in the present study, a consistent finding of the previous study [29]. Hsp 90 is promptly recruited by endothelial stimulation of shear stress induced by ultrasonic waves, and enhances eNOS activation [30].…”
Section: Lipus Ameliorates Cognitive Dysfunctions By Reducing Ab and supporting
confidence: 92%
See 1 more Smart Citation
“…Although the total number of Iba-1-positive microglia decreased by LIPUS, phagocytosis was rather enhanced in the LIPUS-treated group. Besides, Hsp 90, which is known to inhibit aggregation of Ab [28], was enhanced by LIPUS in the present study, a consistent finding of the previous study [29]. Hsp 90 is promptly recruited by endothelial stimulation of shear stress induced by ultrasonic waves, and enhances eNOS activation [30].…”
Section: Lipus Ameliorates Cognitive Dysfunctions By Reducing Ab and supporting
confidence: 92%
“…In the present study, the expression of APP and BACE-1 were significantly decreased by the LIPUS therapy, and Ab was significantly reduced in triton-soluble fraction and histological assessment. Regarding the mechanism of unchanged TBS soluble Ab levels, Ab is known to dissolve in a monomer form at concentrations lower than 3 mM, whereas it aggregates at concentrations higher than 3 mM [29]. In the present study, although the total amount of Ab was actually decreased by LIPUS treatment, more amount of Ab was produced than the amount that could dissolve in extracellular fluid.…”
Section: Lipus Ameliorates Cognitive Dysfunctions By Reducing Ab and mentioning
confidence: 42%
“…By contrast, an HSP90-β inhibitor inhibited tumor growth through apoptosis, inducing cell cycle arrest and downregulating target proteins (38,39). In addition, HSP90-β has been demonstrated to regulate bone metabolism (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that exposure to low‐intensity pulsed ultrasound (LIPUS) accelerates tissue regeneration as a result of enhanced blood circulation, resulting in an acceleration of wound or fracture healing and induction of angiogenesis . Numerous phenomenological studies have shown that a variety of cellular events occur in injured tissues following exposure to LIPUS.…”
mentioning
confidence: 99%